EVALUATION OF THE EFFECTIVENESS OF CHEMOTHERAPY DRUGS IN CERVICAL CANCER PATIENTS IN THE EDELWEISS INPATIENT ROOM RSUD ULIN BANJARMASIN - Idza Julia Nooralifia; Tuty Mulyani (Bajang Institute, 2026)
Cervical cancer is cancer caused by infection with the Human Papilloma Virus (HPV) and one of the treatments is chemotherapy in combination with two or more drugs to increase the destruction of the number of cancer cells. This study aims to determine the patient characteristics, treatment patterns, doses, and evaluating the effectiveness of chemotherapy drugs in cervical cancer patients at the Edelweis Inpatient Installation of RSUD Ulin Banjarmasin. This research is descriptive quantitative research with a cross sectional method. Samples were taken by accidental sampling technique and the total samples were 31 samples. Data collection was carried out using patient medical records. The results of the study included: the characteristics of patients who underwent chemotherapy were at the age of 51-60 years (45.2%); the age at first marriage was mostly at the age of 15-20 years and married once (38.7%); the most stages were stage IIIB (41.9%); The treatment pattern used was a combination of Paclitaxel 230 mg and Carboplatin 450 mg. The effectiveness based on improvement in clinical symptoms in the form of the disappearance of vaginal discharge symptoms (26.9%) and vaginal bleeding symptoms (63%), as well as the decreased scores of pain rating scales. The results showed that chemotherapy was significant in lowering pain scores in cervical cancer patients (p<0.05).